When Saving Time becomes Labor: Time, Work, and Technology in Homecare - Bergschöld, Jenny M. (Nordic Journal of Working Life Studies, 2018)
The article shows how sociomaterial practices of ordering temporality can become part of labor and workers identities, when homecare workers who work with ‘time-saving’ technology experience a lack of sufficient time to do their work. The article offers the concept ‘time labour’ to describe this practice, and defines it as homecare workers methods of saving time, by cutting visits to care recipients as short as possible, and by using technology to strategically produce and maintain quantitative representations of themselves as skilled workers. The term time labor conceptualizes these methods as sociomaterial enactments of temporality that are an intrinsic part of the workers ability to perform that work as well as their ability to produce and maintain a professional identity. The article argues that the role of technology is never predictable, but always emerges in use, and suggests a turn toward domestication theory in practice theoretical studies of work with technology